The Perception of CSSD Staff Regarding Health Conditions, Workload, and Ergonomic Risks - Alrmali, Norah Mofadhi Marshoud; Alrehaili, Yousef Mabruk; Alshammri, Areej Tyeab; Alhejaili, Marwah Talal Dakhel; Alsaedi, Moayad Ibrahim (Journal of Posthumanism, 2025)
Background: The Central Sterile Supply Department (CSSD) is an essential part of the healthcare system, as it sterilizes and ensures the safety of surgical equipment. Nevertheless, the CSSD staff faces significant issues, including workload stress, ergonomic risks, and health concerns, due to the physically intensive nature of their work. Their performance on the job and service quality may be affected by the lack of ergonomic support and the high workload. Aim: This research seeks to identify the perceptions of CSSD employees concerning their health status, workload stress, ergonomic hazards and task execution. Additionally, the study examines the relationships among experience, training, and task performance in the context of CSSD. Method: A quantitative cross-sectional survey was conducted among 71 hospital workers in the CSSD in the Hail health cluster, Saudi Arabia. The participants were given self-administered questionnaires divided into demographics, workload stress, health conditions, ergonomic risks, and task performance. Descriptive and inferential statistics were performed on the data using Pearson’s correlation and linear regression. Result: The study identified workload stress as a significant negative factor affecting both job performance (β = -0.56, p < .01) and service quality (β = -0.24, p < .05) in CSSD employees. It was found that experience (β = 0.42, p < .01) and training (β = 0.39, p < .01) moderated the relationship between workload stress and job performance, improving employee efficiency and well-being. Furthermore, ergonomic risks were shown to negatively impact health, with functional adaptation mediating the effects of these ergonomic hazards on health outcomes (β = -0.30, p < .01). Conclusion: CSSD employees identify significant health and ergonomic stressors that affect their performance and well-being. Training and experience are essential for alleviating the adverse impact of workload stress, and the importance of ergonomic interventions and continuous staff training is underscored.